2004
DOI: 10.1021/jp048279j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Solvent Control of Electron Transfer in a Flexible, Tethered Donor−Acceptor Pair

Abstract: The solvent dependence of the photoinduced intramolecular charge transfer rate constants of 1-(9-anthryl)-3-(4-dimethylaniline)propane (ADMA) is investigated by picosecond time-resolved fluorescence spectroscopy in polar solvents. ADMA undergoes electron transfer by two distinct mechanisms, depending on the solvent polarity. In nonpolar solvents the excited ADMA molecule must fold prior to electron transfer, whereas in polar solvents electron transfer can occur in an extended conformation. In polar solvents, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…Over the past decades, a large number of chemical systems, consisting of covalently linked electron donor (D) and acceptor (A), have been synthesized and investigated to examine electron transfer (ET) reactions and theories with controlled parameters of free energy gap (Δ G ), reorganization energy (λ), and donor–acceptor coupling ( J ) or distance (r). These reactions were usually studied by changing one parameter while the other two parameters were fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, a large number of chemical systems, consisting of covalently linked electron donor (D) and acceptor (A), have been synthesized and investigated to examine electron transfer (ET) reactions and theories with controlled parameters of free energy gap (Δ G ), reorganization energy (λ), and donor–acceptor coupling ( J ) or distance (r). These reactions were usually studied by changing one parameter while the other two parameters were fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a two-dimensional reaction coordinate is used in the description to include both the vibronic couplings and the solvent degrees of freedom . The kinetics of solvent-controlled ET processes has been extensively studied theoretically, , but the existing body of time-dependent studies demonstrating the dynamic solvent control of ET still leaves important fundamental questions open. In this paper, we want to experimentally clarify the impact of solvation on the ET dynamics and how the progress of the solvation influences the ET.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, experimental investigations of the dynamical solvent effect on the reaction dynamics have focused on small organic molecules, ,,,,, metal complexes, ,, and CT to solvent states . To clearly separate the influence of the solvation from the intramolecular properties that determine the speed of ET, molecules are needed which allow ET under favorable conditions faster than the solvation time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Figure exhibits the steady-state emission spectra of both DBA3 and DBA4 in tetrahydrofuran (THF) after excitation of the anthracene moiety at 355 nm. The emission at wavelengths from 375 to 450 nm is from the unquenched, locally excited anthracene moiety . The broad emission at the wavelengths longer than 450 nm is from exciplexes formed after intramolecular electron-transfer quenching of the excited anthracene moiety by the N , N -dimethylaniline moiety.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that, in nonpolar solvents like cyclohexane and n-hexane, the intramolecular electron transfer quenching of DBA3 takes 2−4 ns and can only happen at contact configuration. Wang et al and Kauffman et al have shown that in nonipolar solvents the electron-transfer rate in DBA3 exhibits a power law dependence on viscosity η.…”
Section: Resultsmentioning
confidence: 99%